Racial and ethnic disparities in chronic health conditions among women with a history of gestational diabetes mellitus - Shahrzad Bazargan-Hejazi; Maria Ruiz; Shakir Ullah; Gazala Siddiqui; Maria Bangash; Shahbaz Khan; Wendy Shang; Parissa Moradi; Magda Shaheen (Tabriz University of Medical Sciences, 2021)
Background: This study aims to examine and determine the role of race/ethnicity in chronic conditions in women diagnosed with gestational diabetes mellitus (GDM) during any of their previous pregnancies. Methods: We used the National Health and Nutrition Examination Survey (NHANES) from2007-2016 to identify women who self-reported prior GDM and chronic disease diagnoses such as cardiovascular disease, hypertension, depression, and type 2 diabetes mellitus (T2DM).We used bivariate analysis using the chi-square test (χ²) and multiple logistic regressions to perform statistical test for associations, taking into consideration design and sample weight. Results: Among participants with prior GDM diagnoses, black women had a 74.4% prevalence of chronic disease, followed by Whites, 58.5% Hispanics, 58.0%, and Asians, 51.9% (P=0.009).Black women with prior GDM diagnoses had 2.4 odds of having chronic conditions compared to Whites (adjusted odds ratio [AOR]=2.40, 95% confidence interval [CI] = 1.28-4.50). In addition, they had higher odds of being former smokers (AOR=1.73, 95% CI=1.01-2.96),current smokers (AOR=1.96, 95% CI=1.06-3.61), having a body mass index (BMI) of 25-29.9(AOR=2.55, 95% CI=1.10-5.87), or a BMI ≥30 (AOR=4.09, 95% CI = 2.05-8.17) compared to their White counterparts. Hispanic women had lower odds of being diagnosed with GDM and associated chronic diseases. Conclusion: Black women with GDM were disproportionally affected and at higher risk to be diagnosed with chronic conditions. Smoking and obesity were strongly associated with chronic disease diagnoses. Our findings also suggest a 'Hispanic Paradox', requiring further study. These findings inform primary care clinicians and Obstetricians, and Gynecologists of at-risk patients who could benefit from lifestyle modification recommendations and counseling.